Highly thermo-conductive yet electrically insulating material with perpendicularly engineered assembly of boron nitride nanosheets. (29th September 2021) - Lei, Chuxin; Zhang, Yongzheng; Liu, Dingyao; Xu, Xuran; Wu, Kai; Fu, Qiang
Abstract: With rapid evolution of advanced microelectronic devices, thermally conductive polymeric materials with impressive through-plane thermal conductivity ( κ ⊥ ) and remarkable electrical insulating properties are urgently demanded for efficient thermal management. Assembly of boron nitride nanosheets (BNNS) into polymer matrix with vertically interconnected conformation was usually adopted. However, impeded by inferior oriented degree and insufficient overlapped interconnection of BNNS, polymer/BNNS nanocomposites still suffered from a limited enhancement of κ ⊥ . In this work, we firstly prepared regenerated cellulose (RC)/BNNS filaments with high thermal conductivity via wet-spinning method. Then, a tailored polydimethylsiloxane (PDMS)/(RC/BNNS) filaments nanocomposite with hierarchical assembled architectures is successfully fabricated with customized-mold vacuum impregnation. Numerous bunches of macroscopical hybrid filaments penetrate through the nanocomposite from the bottom to the up, while vertically aligned microscopical BNNS with efficient filler interconnections confined within filaments provide many uniaxial thermal pathways. Attributed to tactfully engineered phonon pathways, the as-prepared material exhibits a remarkable κ ⊥ up to 5.13 W/m K at 27.05 vol% BNNS loading, outperforming the characters in most literatures. Along with excellent electrical resistance and extraordinary thermal management performances, this type of nanocomposite with hierarchical structures provides an effective strategy to thickness-direction heat transfer issues of electronic devices. Graphical abstract: Image 1 Highlights: Engineering the whole-range and vertically aligned BNNS pathways in bulk composites. Excellent through-plane thermal conductivity and electrical insulating property. Impressive thermal management performances for advanced electronic devices.